2022
DOI: 10.3390/polym14142819
|View full text |Cite
|
Sign up to set email alerts
|

A Green Resin Wood Adhesive from Synthetic Polyamide Crosslinking with Glyoxal

Abstract: Glyoxal is considered to be the most likely substitute for formaldehyde to synthesize resin adhesives for wood bonding due to its reactivity, structural characteristics, being non-toxic, low volatility, and acceptable cost. Regrettably, the performance of the resin synthesized using glyoxal to directly replace all formaldehyde is not totally satisfactory, especially as it has almost no water resistance. This makes such a simple alternative fail to be suitable for industrial production. To prepare an environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Further, MHG resins are also unique because they are highly resistant to boiling water as boiling water soaking bonding strength has never been reported for other glyoxal-related adhesives. According to the results in the literature, ,,,, only dry bonding strengths of plywood were reported for pure MG and UG, and a few studies reported cold water soaking bonding strengths. ,, As for other composite adhesives, to make them more stable toward hydrolysis, more components were used with glyoxal, such as oxidized cassava starch and polyethyleneimine (PEI), leading to, namely, UG-oxidized cassava starch (UGCS) and polyethyleneimine-UG (HBPEIUG) adhesives. Note that PEI is also a branched polyamine containing terminal amino groups.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Further, MHG resins are also unique because they are highly resistant to boiling water as boiling water soaking bonding strength has never been reported for other glyoxal-related adhesives. According to the results in the literature, ,,,, only dry bonding strengths of plywood were reported for pure MG and UG, and a few studies reported cold water soaking bonding strengths. ,, As for other composite adhesives, to make them more stable toward hydrolysis, more components were used with glyoxal, such as oxidized cassava starch and polyethyleneimine (PEI), leading to, namely, UG-oxidized cassava starch (UGCS) and polyethyleneimine-UG (HBPEIUG) adhesives. Note that PEI is also a branched polyamine containing terminal amino groups.…”
Section: Results and Discussionmentioning
confidence: 99%
“…HMDA, also named 1,6-hexanediamine or 1,6-diaminohexane, serves as a precursor for the production of nylon-6,6 and various resins [44,120]. Beyond its application in nylon production, HMDA is also utilized in the textile and water treatment industries [120]. So far, some whole-cell bioconversion approaches were reported for its production.…”
Section: 6-hexamethylenediamine (Hmda)mentioning
confidence: 99%
“…Many commercial aldehyde crosslinkers, including glyoxal, glutaraldehyde, and formaldehyde, have been studied and commonly applied in wood-based composite materials and resins to enhance their strength and water resistance. [20][21][22][23][24] Chabba and Netravali found that crosslinking soy protein concentrate-based (SPC) resins with 10% (w/w) glutaraldehyde increased the fracture stress and Young's modulus by 20% and 35%, respectively, along with improvement in moisture resistance. 25 When modified with 5% (w/w) formaldehyde, SPI films significantly increased tensile strength by about 20% and Young's modulus by 15%.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, researchers have successfully crosslinked soy protein‐based resins, using external crosslinkers, to enhance their mechanical and thermal properties while minimizing moisture absorption. Many commercial aldehyde crosslinkers, including glyoxal, glutaraldehyde, and formaldehyde, have been studied and commonly applied in wood‐based composite materials and resins to enhance their strength and water resistance 20–24 . Chabba and Netravali found that crosslinking soy protein concentrate‐based (SPC) resins with 10% (w/w) glutaraldehyde increased the fracture stress and Young's modulus by 20% and 35%, respectively, along with improvement in moisture resistance 25 .…”
Section: Introductionmentioning
confidence: 99%